Cane Ridge in Context Perspectives on Barton W. Stone and the Revival - Dunnavant, Anthony L. (Disciples of Christ Historical Society, 1992)
The year 1991 was the 200th anniversary year of the construction of the Cane Ridge Meetinghouse by a Presbyterian congregation in frontier Kentucky. To celebrate this event, the Disciples of Christ Historical Society hosted a number of special events, including lectures and addresses on the legacy of Barton W. Stone as well as on the background and meaning of the revival. This volume brings together several of these addresses and the chapters are arranged to proceed from reflections upon the various ways Barton W. Stone has been remembered in the Stone-Campbell traditions. Contributors include Anthony L. Dunnavant, Richard L. Harrison Jr, Paul Blowers, C. Leonard Allen, D. Newell Williams, Ronald P. Byars, Newton B. Fowler, Samuel S. Hill, and Howard E. Short.